Política de drogas e subjetividade: contribuições das perspectivas de Michel Foucault e da biopolítica para os discursos contra(a)dictos - Rodrigues, Rita de Cássia Rebouças (2016)
The phenomenon of the use of alcohol and other drugs made illegal, raises today, a difficult debate, almost outlawed. It presents itself as a serious and complex problem of public health, legal and legal implications. This study aimed to reflect on alcohol policies and other drugs in Brazil, analyzing their construction processes in the historical context through the concept of biopolitics (biopower) Michel Foucault. This is a qualitative research through case study, with the framework of discourse analysis as a method, a historical and anthropological perspective. The aim was to understand the speeches built on drugs, primarily for the use of the drug / drug in the context of the health-disease; then sought to assess how the current drug policy was established based on the prohibition and criminalization made illicit substances through international agreements, followed by most countries, configured as a war against drugs is essentially a war against people who use drugs. To enter the discussion of subjectivity, the body is considered as the object of interventions in the fields of medicine and the state, without, however, fail to glimpse it as imbued with history, culture and even subjectivity. After all, the study deals with a phenomenon that is here the object of the public health field, can not be dissociated from other knowledge. Object of study by Michel Foucault, the body is designed as "registration surface of events", crossed and ruined by history. Foucault runs by unveiling paths of the official discourse, which aims to ordering of society, speech is subtract the right of the subject to his own body. Put the body in the State field, and this having on that control governed by the power of speech, Foucault calls biopolitics this relationship that has the biological and life in governance strategies, and therefore it produces racism. Racism that results in demarcation, in the biological field, among the bodies that should live and who should die bodies. Next, since entering the anthropological field, broadening the discussion of racism and exclusion process and proscription, the concept of ethnocide is used to highlight the role of repressive policies on the use and the drug trade in Brazil, and have caused in recent decades, more negative consequences than actually the consumption of drugs themselves.